DNA Virus Detection in Olfactory Neuroblastomas Using Targeted Enrichment NGS - Jauhiainen, Maria K; Mielonen, Outi I; Haapaniemi, Aaro; Söderlund-Venermo, Maria; Hagström, Jaana; Perdomo, Maria F; Sinkkonen, Saku T; Mäkitie, Antti A (Japan, 2026)
A variety of malignancies can be found in the sinonasal tract including the nasal cavity, paranasal sinuses, and skull base. Many of these are attributed to viruses, for example, carcinomas with the presence of transcriptionally active high-risk human papillomavirus, as well as Epstein-Barr virus associated malignant lymphoepithelial carcinoma and haematolymphoid neoplasias. Olfactory neuroblastoma (ONB) is a rare malignant tumor of the olfactory fossa with an unknown etiology. We present the first comprehensive virus study of ONB. By targeted next-generation sequencing for 41 DNA viruses, we investigated the presence of papillomaviruses, herpesviruses, polyomaviruses, and parvoviruses, among others, in 12 ONBs. In addition, herpesvirus presence was evaluated by qPCR. Low-risk HPV6 was detected in one sample. Human endogenous retroviruses were positive in all samples, supporting successful library preparation and sequencing, considered as an internal quality control. No other virus findings were observed. The present broad-scale virus study did not reveal abundant presence of viral DNA in ONB suggesting a limited viral role in its etiology. Nevertheless, our cohort exhibited a finding of low-risk HPV, which has been associated with increased risk of cancer progression of inverted sinonasal papilloma in the same anatomic site advocating for further research. Trial Registration: §31/07.03.2019.